Quality assurance for increasing growth monitoring and promotion (GMP) performance - Oktora Wahyu; Endy Paryanto; Tonny Sadjimin (Paediatrica Indonesiana, 2007)
Background Measuring body weight of under-five children is oneof the Family Nutritional Improvement Program or UsahaPerbaikan Gizi Keluarga (UPGK) activities which was integratedin Integrated Health Post (Posyandu) activities. Growthmonitoring and promotion (GMP) has been used as the maincomponent of the health and nutritional program in severaldeveloping countries. Unfortunately, this activity did not run asexpected. This study aimed to understand how quality assurance/total quality management (QA/TQM) influence the performanceof the GMP.Methods This 6 month operational research included 76 Posyandusin four subdistricts of Jogyakarta Province. The results of thePosyandus’s GMP score performance were used as a basis toimprove the performance for the next consecutive months withQA system. Data were transformed as a score index. Student’s t-test was used to analyze the data.Results The quality assurance could increase the performance ofGMP, which was done in Posyandus intervention group for 3consecutive months. The baseline scores for both groups were0.47±0.12 vs 0.42±0.17 (P=0.302), at the second monthmonitoring: 0.58±0.07 vs 0.42±0.16, for the intervention group(P<0.001). The mothers’ index (percentage of the children underfive attendance and mothers who brought KMS at weighingsession), however, did not significantly change.Conclusion Total quality management increased the generalperformance of Posyandus, but the program could not influencethe mothers’ index.